Quantification and Qualification of Bacteria Trapped in Chewed Gum - Wessel, Stefan W.; van der Mei, Henny C.; Morando, David; Slomp, Anje M.; van de Belt-Gritter, Betsy; Maitra, Amarnath; Busscher, Henk J. (PLOS ONE, 2015)
Chewing of gum contributes to the maintenance of oral health. Many oral diseases, including caries and periodontal disease, are caused by bacteria. However, it is unknown whether chewing of gum can remove bacteria from the oral cavity. Here, we hypothesize that chewing of gum can trap bacteria and remove them from the oral cavity. To test this hypothesis, we developed two methods to quantify numbers of bacteria trapped in chewed gum. In the first method, known numbers of bacteria were finger-chewed into gum and chewed gums were molded to standard dimensions, sonicated and plated to determine numbers of colony-forming-units incorporated, yielding calibration curves of colony-forming-units retrieved versus finger-chewed in. In a second method, calibration curves were created by finger-chewing known numbers of bacteria into gum and subsequently dissolving the gum in a mixture of chloroform and tris-ethylenediaminetetraacetic-acid (TE)-buffer. The TE-buffer was analyzed using quantitative Polymerase-Chain-Reaction (qPCR), yielding calibration curves of total numbers of bacteria versus finger-chewed in. Next, five volunteers were requested to chew gum up to 10 min after which numbers of colony-forming-units and total numbers of bacteria trapped in chewed gum were determined using the above methods. The qPCR method, involving both dead and live bacteria yielded higher numbers of retrieved bacteria than plating, involving only viable bacteria. Numbers of trapped bacteria were maximal during initial chewing after which a slow decrease over time up to 10 min was observed. Around 108 bacteria were detected per gum piece depending on the method and gum considered. The number of species trapped in chewed gum increased with chewing time. Trapped bacteria were clearly visualized in chewed gum using scanning-electron-microscopy. Summarizing, using novel methods to quantify and qualify oral bacteria trapped in chewed gum, the hypothesis is confirmed that chewing of gum can trap and remove bacteria from the oral cavity.